Pengaruh Audit Operasional dan Pengendalian Internal terhadap Kinerja Perusahaan - Risma Adelia Yuningsih; Suwandi Suwandi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The company is the place where all production activities occur and all production factors gather. One important factor for a company to achieve quality performance is from a non-financial perspective such as operational audits and internal controls. This research aims to analyze the influence of operational audit and internal control on the performance of PT. Karya Sidorukun Santosa. The method used in this research is a quantitative approach with data obtained through distributing questionnaires. The results of data analysis show that operational audits have a negative effect on company performance, while internal control has a positive effect on company performance.